2012
DOI: 10.1002/elps.201100615
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex quantitative foodborne pathogen detection using high resolution CESSCP coupled stuffer‐free multiplex ligation‐dependent probe amplification

Abstract: Sensitive multiplex detection methods for foodborne pathogens are important in controlling food safety, and detection of genetic markers is accepted to be one of the best tools for sensitive detection. Although CE technology offers great potential in terms of sensitive multiplex detection, the necessary amplification is confined to markers sharing common primers such as the 16S rRNA gene. For precise and sensitive detection, pathogen-specific genes are optimal markers. Although multiplex ligation-dependent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 21 publications
(19 reference statements)
0
27
0
Order By: Relevance
“…Long stuffer sequences affect the quantitative consistency because the amplification efficiency fluctuates between short and long products. Thus, Chung et al [65] developed stuffer-free MLPA-CE-SSCP to sensitively detect 10 foodborne pathogens. All 10 pathogens were reliably identified, with LODs of 0.5-5 pg of genomic DNA.…”
Section: Detecting and Diagnosing Bacteriamentioning
confidence: 99%
“…Long stuffer sequences affect the quantitative consistency because the amplification efficiency fluctuates between short and long products. Thus, Chung et al [65] developed stuffer-free MLPA-CE-SSCP to sensitively detect 10 foodborne pathogens. All 10 pathogens were reliably identified, with LODs of 0.5-5 pg of genomic DNA.…”
Section: Detecting and Diagnosing Bacteriamentioning
confidence: 99%
“…To detect multiple GFL products, CE-SSCP with highly enhanced resolution and separation was adopted. GFL products could be separated according to their unique folding structures depending on the sequence variations in the capillary filled with poly (ethyleneoxide)–poly (propyleneoxide)–poly (ethyleneoxide) (PEO-PPO-PEO) triblock copolymer, which we previously reported262728. To establish this MDR/XDR-TB detection system, we selected highly polymorphic regions as targets for multiplex detection (Table 1).…”
mentioning
confidence: 99%
“…Several studies have shown that MLPA can be applied to identify and characterize multiple microorganisms (Bergval et al, 2008, Chung et al, 2012, Terefework et al, 2008, Wolffs et al, 2009. Although MLPA has been used in many clinical applications, its disadvantages limit the general use of this technique in clinical laboratories.…”
mentioning
confidence: 99%